Qualitative study of roles of religious leaders in promoting adolescent sexual reproductive health and rights in Iganga municipality Uganda - Baturaine Barbara, Nayebare; Kizito, Omona (International Journal of Medicine, 2021)
Introduction: Young people in adolescent stage are very vulnerable. Sexual and reproductive health choices they make as they transition from childhood to adulthood determine a lot about their well-being.Objective: To assess the role of religious leaders in promoting adolescent sexual and reproductive health rights in Iganga Municipality.Methodology: Qualitative phenomenological design was used. Sample of 30 participants (25religious leaders and 5adolescents) were interviewed. Data was collected using in-depth interviews, transcribed, coded and analyzed using thematic content analysis.Results: Information shared by religious leaders to adolescents helped them to live responsible lives. Results also indicated that; religious leaders perceived promotion of ASRHR to imply elevation of sexual immorality. Religious leaders had both protective and preventive influences on promotion of ASRHR.Conclusion: Religious leaders greatly contribute to promotion of ASRHR by enhancing information sharing. Dialogues, therefore, enhances their awareness about ASRHR and gives them confidence to address the matter with adolescents.Â Â Â
Keywords: Adolescent Sexual and Reproductive Health and Rights (ASRHR); Adolescents; Religious leaders.